Analytical studies on the Oxidation of S-containing Amino Acids with Pentavalent Vanadium Reagent - Chauhan, R.P.S.; Khan, M.A.; Khan, I.A. (Asian Journal of Chemistry, 2010)
A simple, quick and convenient method has been developed for themicro estimation of S-containing amino acids. The sample 1-5 mg isallowed to react with 2 mL of 0.3 N ammonium metavanadate(V) reagentand 10 mL of 10 N H2SO4 was added before the reaction helps in detectingthe end point. The unconsumed reagent can be accurately titrated with0.025 N ferrous ammonium sulphate solution using N-phenyl anthranilicacid as indicator. Standard deviation as well as coefficient of variation wascalculated for reproducible and accurate result. The accuracy of the methodis within ± 1%.